A brief revision of brachypterous Phaneropterinae of the tropical Andes (Orthoptera, Tettigoniidae, Odonturini) - Braun, Holger (Zootaxa, 2011)
The main purpose of this paper is the description of two very tiny, long-legged, and short-winged katydids from the eastern slope of the eastern Andean cordillera of south-east Ecuador, Nanoleptopoda nigrifrons gen. et sp. nov. and N. albifrons sp. nov., the first species along with its ultrasound calling song. The monospecific and closely-related genus Parangara is included in Odonturini. Dichopetala inca and Anisophya equatorialis are transferred under the so far monospecific genus Cohnia, so that now the tribe includes three genera with six species from the tropical Andes. The ecological background of wing reduction in relation to elevation is briefly discussed.